HOLISTICS JOURNAL - Holistics Journal (Politeknik Negeri Sriwijaya, 2019)
Holistics Journal is published twice a year in the month of June and December (p-ISSN 2085-4021│e-ISSN 2657-1897); it presents articles on hospitality, linguistics, and literature. The contents include analyses, studies, application of theories, research reports, materials development, and reviews.